Projecting irrigation demand under IPCC climate change scenarios using WEAP modeling in the Rechna Doab, Pakistan - Hilal Khan; Zamil Bin Zahid (Cleaner Water)
Pakistan is currently facing significant water scarcity issues, intensified by climate change. The main water source, the transboundary Indus River system, faces challenges such as water management, limited data availability, and inadequate management, leading to a gap between water demand and supply across various sectors. Agriculture, which consumes over 95 % of the country’s water resources, contributes nearly 25 % to the GDP, but is heavily dependent on irrigation due to limited rainfall. With rainfall meeting only 15 % of crop water requirements, groundwater plays a critical role, covering 40–60 % of irrigation needs. This study focuses on the Rechna Doab in the Indus Basin Irrigation System (IBIS) using the WEAP (Water Evaluation and Planning) model to assess the supply-demand gap under IPCC's climate change scenarios from Assessment Report Six (AR6). The main findings indicate: (1) Under SSP 8.5, unmet demand in the Upper Chenab Canal and other regions will increase by 33–47 % by mid-century; (2) demand site coverage will decline significantly, especially in Lower Gugera and Jhang branches; (3) groundwater dependency will increase substantially in response to the growing supply-demand gap. This work contributes to improving water management in Rechna Doab by providing a clear framework for adapting water resources to climate change using WEAP projections under various IPCC scenarios.